Heart transplantation in a patient with primary malignant tumor - E. E. Kliver; I. S. Murashov; A. M. Volkov; E. N. Kliver; D. V. Doronin (Вестник трансплантологии и искусственных органов)
The article looks at a clinical case of a 31-year-old female with signs of paroxysmal ventricular tachycardia and Morgagni–Adams–Stokes syndrome. In April 2014, electrophysiological examination revealed a source of ventricular tachycardia localized in the apices of the right and left ventricles of the patient. The sources were then subjected to RF ablation followed by cardioverter-defibrillator implantation. Subsequent antiarrhythmic therapy failed to improve her state. In September 2016 the patient was re-examined and underwent RF ablation of the apical region of the right ventricle. Later on, taking into account continuously recurrent life-threatening cardiac rhythm disorders, as well as unpromising strategies for further conservative treatment, she was put on the waiting list and then underwent orthotopic cardiac transplantation. Histological examination and immunohistochemistry assay showed leiomyosarcoma in the source of ventricular tachycardia previously found in the apex of the right ventricle. This clinical case demonstrates a diversity of clinical manifestations of primary malignant tumors of the heart that pose a challenge for intravital diagnostics and interpretation of a clinical picture.